Efektivitas Kinerja Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Natuna - Adi Putra, Dimas; Syaprianto (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This study discusses the public service process, which is an interaction relationship between two elements, namely the government and the public. The problem formulated is the scarcity of resources and budget limitations in the implementation of public services. The research methods used in this research are observation and interviews. The aim of this research is to determine the effectiveness of the performance of the Natuna Regency Population and Civil Registration Service. The research location is at the Population and Civil Registration Service in Natuna Regency. The results of the research show that it takes quite a long time to search for incoming mail, outgoing mail and official mail as well as storing mail documents on shelves which can cause the mail to be lost or easily damaged. Therefore, human resource development is carried out by providing employees with special training in the application of information systems in the process of completing work in the office, such as the work of archiving incoming and outgoing letters. Communities who can work together and understand every service process will ensure that there are no delays or other problems with the Natuna Regency Dukcapil Service System. Natuna Regency has made innovations to get better services.